Coati Optimization Algorithm: A new bio-inspired metaheuristic algorithm for solving optimization problems - Dehghani, Mohammad; Montazeri, Zeinab; Trojovská, Eva; Trojovský, Pavel (Knowledge-based systems, 2023)
In this paper, a new metaheuristic algorithm called the Coati Optimization Algorithm (COA) is introduced, which mimics coati behavior in nature. The fundamental idea of COA is the simulation of the two natural behaviors of coatis: (i) their behavior when attacking and hunting iguanas and (ii) their escape from predators. The implementation steps of COA are described and mathematically modeled in two phases of exploration and exploitation. COA performance is evaluated on fifty-one objective functions, including twenty-nine functions from the IEEE CEC-2017 test suite and twenty-two real-world applications from the IEEE CEC-2011 test suite. COA’s results are compared to those of eleven well-known metaheuristic algorithms. The simulation results indicate that COA has an evident superiority over the compared algorithms by balancing exploration in global search and exploitation in local search, and is far more competitive. To assess the COA’s effectiveness in real-world applications, the proposed approach is implemented on the IEEE CEC-2011 test functions and four practical optimization problems, which the simulation results indicate the high capability of COA in dealing with these types of optimization problems. •A new optimization algorithm called Coati Optimization Algorithm (COA) is designed to model the natural behaviors of coatis.•COA’s fundamental inspirations include attacking and hunting coatis and the escape behavior of coatis when confronted by predators.•The various stages of COA are described, then mathematically modeled in two phases of exploration and exploitation.•Sixty-eight standard benchmark functions have been employed to evaluate COA performance in solving optimization problems.•The performance of the COA in presenting the optimization results is compared with eight well-known metaheuristic algorithms.